Rings without a lord? Enigmatic fossils from the lower Palaeozoic of Bohemia and the Carnic Alps. (19th February 2013) - Ferretti, Annalisa; Cardini, Andrea; Crampton, James S.; Serpagli, Enrico; Sheets, H. David; Štorch, Petr
<x xml:space="preserve">Abstract</x> Fossilized ring‐like structures with enigmatic function and taxonomic affiliation were recovered for the first time from the Upper Ordovician of the Carnic Alps and the Silurian of Bohemia. These rings, already mentioned as minor constituents in previous conodont studies (e.g. Webers 1966, p. 1; Bischoff 1973, p. 147), were reported from the Palaeozoic of several regions in Europe and North America. Originally considered as inwardly accreted adhering discs of a benthic hyolithelminth worm with a phosphatic tubular projection, they were later reinterpreted in relation to a putative crinoid epibiont or even as possible scyphozoans. Despite a long debate, neither the function of the enigmatic Palaeozoic rings nor their taxonomic affiliation has been fully clarified. The studied material, extracted by a standard technique in use for conodonts, consists of 235 elements from 16 stratigraphic levels in the Plöcken Formation (Carnic Alps, Cellon Section; Amorphognathus ordovicicus Biozone, Hirnantian, Ordovician) and in the Kopanina Formation (Bohemia, Mušlovka Quarry; Polygnathoides siluricus Biozone, Ludfordian, Silurian). To explore whether ring size and shape changed over time, we employed a novel combination of geometric morphometric approaches for outlines with no 'homologous' landmarks and showed that only size appreciably varied with an increase of ca. 20%. The emerging data from this study are consistent with the interpretation of the rings as an adhering structure of a benthic organism living on a relatively uniform hard substrate.